Kinerja Sistem Pengolahan Air Limbah Domestik Terpusat Pada Kabupaten Padang Pariaman - Dalfi, Adi; Rita, Eva; Khadavi, Khadavi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
The national achievement of access to proper sanitation has not yet been achieved and is aligned with the Sustainable Development Goals (SDG's) target, one of which is